2021
DOI: 10.5433/1679-0359.2021v42n5p2867
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Lawsonia intracellularis in horses raised in three regions of the state of Paraná, Brazil

Abstract: Lawsonia intracellularis is a bacterium already described in several species and most prevalent in pigs, in which it causes enteric problems. Horses can also be affected, developing a disease known as equine proliferative enteropathy, which results from the proliferation of intestinal crypt cells in response to infection by the bacterium. Despite the existence of reports of the disease in several countries, including Brazil, there are still no reports of the disease or epidemiological studies of its occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…In the same study, fecal shedding was found to be 3.14 % by PCR. A recent study in Brazil demonstrated similar seropositivity (5.55 %) and fecal shedding (4.32 %) (2). A recent study conducted in Israel found close results to the present study with 30.5 % and 0.7 % horses positive by ELISA and PCR, respectively (18).…”
Section: Discussionsupporting
confidence: 88%
“…In the same study, fecal shedding was found to be 3.14 % by PCR. A recent study in Brazil demonstrated similar seropositivity (5.55 %) and fecal shedding (4.32 %) (2). A recent study conducted in Israel found close results to the present study with 30.5 % and 0.7 % horses positive by ELISA and PCR, respectively (18).…”
Section: Discussionsupporting
confidence: 88%
“…Etkene bağlı hastalıklar ilk tespit edildiğinden bugüne kadar sporadik olgular ve salgınlar şeklinde birçok kez raporlanmıştır. Son yıllarda da sıklıkla sütten yeni kesilen taylar başta olmak üzere ara sıra erişkin atlarda raporlanan bir hastalık olarak, Amerika Birleşik Devletleri (ABD), Kanada, Brazilya, Japonya, Güney Kore ve Türkiye dahil olmak üzere Avrupa'da raporlanmış ve dünya çapında bir yaygınlığa ulaştığı görülmüştür (3,5,(6)(7)(8)(9)(10).…”
Section: Etiyolojiunclassified